2019
DOI: 10.1111/1759-7714.13275
|View full text |Cite
|
Sign up to set email alerts
|

Management of immune checkpoint inhibitor‐related dermatologic adverse events

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment. The unique spectrum of immune-related adverse events (IrAEs) may occur during treatment. Dermatologic toxicities appear to be one of the most prevalent immunotherapy-related adverse events. The most common symptoms are maculopapular rash and pruritus. Serious dermatologic toxicities including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug reactions with eosinophilia and systemic symptoms are rare. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Dermatologic toxicities are among the most common immune-related adverse events encountered in daily practice when treating lung cancer with an estimated incidence of 44% following CTLA-4 inhibition and 34% with PD-1/PD-L1 targeting treatment ( 23 ). Early data have previously suggested that similarity between tumor antigen and somatic epitopes within the skin and fascia may provide a mechanistic explanation for the occurrence of dermatologic events ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic toxicities are among the most common immune-related adverse events encountered in daily practice when treating lung cancer with an estimated incidence of 44% following CTLA-4 inhibition and 34% with PD-1/PD-L1 targeting treatment ( 23 ). Early data have previously suggested that similarity between tumor antigen and somatic epitopes within the skin and fascia may provide a mechanistic explanation for the occurrence of dermatologic events ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SJS was assessed to be grade 3 by CTCAE v5.0. The literature recommends complete cessation of the inducing drug, and immunoglobulin or corticosteroid is recommended to treat SJS along with supportive and symptomatic management (13)(14)(15). Although there was a possibility that SJS could be related to the enzalutamide dose, enzalutamide was discontinued immediately, considering SJS is a serious skin reaction and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously proposed that immunotherapies emerge as a trigger for SCARs, as immune checkpoint inhibition may predispose patients to skin hypersensitivity 32,53–55 . Thus, in addition to drug discontinuation and supportive care, these denominated immune‐related SCAR‐like reactions, may be treated mainly with corticosteroids 56,57 , 58–60 . Conversely, no high evidence‐level guidelines exist for targeted therapies‐induced SCARs; therefore, they may be managed in the same directions as regular SCARs.…”
Section: Discussionmentioning
confidence: 99%